Multivariate sar studies on some novel drug precursor benzothiazolinone derivatives - Gülseven Sıdır, Yadigar; Sıdır, İsa; Güney, İbrahim; Güney, İbrahim (Anadolu Üniversitesi, 2015)
Multivariate structure-activity relationships of new modeled thirty two antinociceptive active benzothiazolinone derivatives have been investigated by using two different chemometrics methods, principal component analysis (PCA) and hierarchical cluster analysis (HCA), for rating biological activities. Twenty Molecular descriptors, which indicate electronic, termochemical and hydrophobic properties of molecules, are calculated by means of Austin Model (AM1) and density functional theory (DFT). The PCA and HCA methods are applied with polarizability (α), electrophilic index (ω) and heat of formation in aqueous phase (HOFAqueous). The results are found quite efficient to classify the thirty two compounds in two groups to be active and inactive. The correlation matrix and variable weight have been used to explain of relationships between calculated physicochemical parameters of molecules. Adding F and OCH3 substituents to main ring of the investigated compounds and lengthening in alkyl group located on piperazine changes the biological activity.

Yeni modellenen analjezik aktif otuziki benzotiyazolinon türevinin çok değişkenli yapı-aktivite ilişkileri iki farklı kemometric metot olan temel bileşen analizi (PCA) ve hiyerarşik kümeleme analizi (HCA) kullanılarak incelendi. Moleküllerin elektronik, termokimyasal ve hidrofobik özelliklerini tanımlayan yirmi moleküler tanımlayıcı Austin Modeli (AM1) ve yoğunluk fonksiyonel teorisi (DFT) kullanılarak hesaplandı. HCA ve PCA metotları sıvı fazdaki (HOFSıvı) polarizebilite (α), elektrofilik indis (ω) ve oluşum ısısı ile uygulanır. Sonuçlar otuziki molekülü aktifve inaktif olarak iki grupta sınıflandırmak için oldukça etkili bulundu. Korelasyon matrisi ve değişken ağırlığı moleküllerin hesaplanan fizikokimyasal parametreleri arasındaki ilişkileri açıklamak için kullanıldı. İncelenen bileşiklerin ana halkasına F ve OCH3 sübstitüentlerin eklenmesi ve piperazin üzerindeki alkil gurubunun uzaması biyolojik aktiviteyi değiştir.
Bazı yeni ilaç öncüsü benzotiyazolinon türevleri üzerine çok değişkenli sar çalışmaları
Keywords: NSAI drug; Benzothiazolinone; Multivariate SAR; Principal component analysis (PCA); Hierarchical cluster analysis (HCA); NSAI ilaç; Benzotiyazolinon; Çok değişkenli SAR; Temel bileşen analizi (PCA); Hiyerarşik kümeleme analizi (HCA)